THERAPY FOR ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION PATIENTS WHO PRESENT LATE OR ARE INELIGIBLE FOR REPERFUSION - M. Cohen; C. Boiangiu; M. Abidi; N. S. Chipigina (Столичная издательская компания, 2016)
Therapy for ST-segment elevation myocardial infarction patients who present late or are ineligible for reperfusion.